ANALISIS POTENSI PENERAPAN KERJASAMA PEMERINTAH SWASTA (KPS) DALAM PENGEMBANGAN INFRASTRUKTUR TRANSPORTASI DI PERKOTAAN (Studi Kasus Kota Semarang) - Eri Setianto Kurniawan; Bambang Pudjianto; Y.I. Wicaksono (Diponegoro University, 2009)
The role of Local Government (Province and District / City) become very important in creating atransportation infrastructure that can support a regional transportation activities and implementing thePublic Private Partnership (PPP) model as an alternative financing strategies other than APBN / APBD.The purpose and goal of this research is to conduct a comprehensive study in order to obtain a picture of thepotential level of urban transport infrastructure development (case study of Semarang City) who performedwith the Public Private Partnership (PPP) model, viewed from the perspective of related stakesholder.Research methodology using descriptive statistical approach and SWOT analysis with the matrix space model.The research concluded that the potential application of PPP policies in the development of transportationinfrastructure in the city of Semarang is located at the conservative level, which means that although there area number of external strategic factors which potentially threat to the implementation of the PPP policies,there is still a commissioner of the strength of internal factors that can be optimized.